2018
DOI: 10.1111/1471-0307.12552
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and survival of Listeria monocytogenes in various types of cheese—A review

Abstract: Since the publication of Regulation (EC) N°2073/2005, ready-to-eat (RTE) food allowing the development of Listeria monocytogenes, including cheese, has to be free of this pathogen in 25 g of product. This review was carried out to gather studies on the prevalence of the pathogen in various types of cheese in Europe, while also including data from other continents. Given that Regulation (EC) N°2073/2005 distinguishes cheeses allowing or not the survival of L. monocytogenes based on the food's pH and water activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
28
5
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 101 publications
(155 reference statements)
4
28
5
1
Order By: Relevance
“…A similar trend was observed in the current study with occurrence of 2.4% in meat and 1.3% in seafood. The occurrence of L. monocytogenes in raw meat, milk, and cheese in this study was lower than that found in other countries [4,11,16,[39][40][41][42][43][44][45]. The global L. monocytogenes population diversity in the implicated food vehicles could be attributed to several factors: (i) improvements in detection methodologies, (ii) packing facility, (iii) increases in populations of lactic acid bacteria, yeasts, and molds that might have an impact on the microenvironment supporting growth of L. monocytogenes, (iv) period and temperature degree of the storage condition, (v) handling by the consumers, (vi) unhygienic conditions, (vii) uncontrolled temperature, (viii) glove/hand issues, (ix) environmental (hygienic conditions of the farms, hygienic conditions of the slaughter houses, rodents, workers, the slicer, trash handling, and cleanup operations) contamination and subsequent cross contamination to other products, (x) transport, (xi) in the processing facilities, and (xii) during handling at the outlets.…”
Section: Discussioncontrasting
confidence: 75%
See 2 more Smart Citations
“…A similar trend was observed in the current study with occurrence of 2.4% in meat and 1.3% in seafood. The occurrence of L. monocytogenes in raw meat, milk, and cheese in this study was lower than that found in other countries [4,11,16,[39][40][41][42][43][44][45]. The global L. monocytogenes population diversity in the implicated food vehicles could be attributed to several factors: (i) improvements in detection methodologies, (ii) packing facility, (iii) increases in populations of lactic acid bacteria, yeasts, and molds that might have an impact on the microenvironment supporting growth of L. monocytogenes, (iv) period and temperature degree of the storage condition, (v) handling by the consumers, (vi) unhygienic conditions, (vii) uncontrolled temperature, (viii) glove/hand issues, (ix) environmental (hygienic conditions of the farms, hygienic conditions of the slaughter houses, rodents, workers, the slicer, trash handling, and cleanup operations) contamination and subsequent cross contamination to other products, (x) transport, (xi) in the processing facilities, and (xii) during handling at the outlets.…”
Section: Discussioncontrasting
confidence: 75%
“…The general low prevalence of L. monocytogenes of less than one percent detected within this study is lower than previous studies, which reflects increased awareness, vigilance, and good practices in food preparation in the Egyptian community in the area of study [3,9,11,[36][37][38][39][40][41]. A recent study by Leong et al [42] of small food businesses in Ireland showed a similar decrease over the course of a three-year study.…”
Section: Discussionsupporting
confidence: 40%
See 1 more Smart Citation
“…However, this approach is very elementary. In this sense, to understand the survival of L. monocytogenes in dairy products during processing, challenge tests can be performed, which means the inoculation of the pathogen during the processing and testing its growth, which can determine the point at which the growth reaches unacceptable levels in a specific product [100]. The use of quantitative food microbiology tools, such as predictive microbiology, constitutes an interesting approach and should be encouraged for the dairy industry, mainly to establish the protective role of lactic bacteria regarding the survival and growth of L. monocytogenes in dairy products [101].…”
Section: Technological Approaches For Inactivation Of L Monocytogenementioning
confidence: 99%
“…In Europe, the first reported listeriosis outbreak was associated with fresh cheese (Linnan et al, 1988) and from an EU baseline survey (EFSA, 2013), there are 0.47% sample of cheese at retail tested positive for L. monocytogenes. Furthermore, there was another study in Turkey demonstrated that the risk of L. monocytogenes contamination in dairy products was still low, by which only two cheese samples positive for L. monocytogenes (2.35%) but none from the raw milk (0%) (Aygun and Pehlivanlar, 2006).The survival of L. monocytogenes can be varied according to different types of cheese, for example the growth of the pathogen is quite impossible in the hard cheese compared with soft or semi-soft cheeses due to lower pH and moisture content (Gérard et al, 2018). For example, a study showed that 41.17% isolates of L. monocytogenes harbored the serotypes, 1/2a, 1/2b and 4b, from a Brazilian soft cheese (Da Silva et al, 1998).…”
Section: Dairy Productsmentioning
confidence: 99%